Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's solve the equation [tex]\(\frac{x-1}{2} = \frac{x+2}{5}\)[/tex] step by step.
1. Start with the given equation:
[tex]\[ \frac{x-1}{2} = \frac{x+2}{5} \][/tex]
2. Eliminate the fractions by finding a common denominator, which is 10 in this case. Multiply both sides of the equation by 10:
[tex]\[ 10 \cdot \frac{x-1}{2} = 10 \cdot \frac{x+2}{5} \][/tex]
3. Simplify both sides:
[tex]\[ 5(x - 1) = 2(x + 2) \][/tex]
4. Distribute the constants on both sides of the equation:
[tex]\[ 5x - 5 = 2x + 4 \][/tex]
5. Move all terms involving [tex]\(x\)[/tex] to one side of the equation and constants to the other side. Subtract [tex]\(2x\)[/tex] from both sides:
[tex]\[ 5x - 2x - 5 = 4 \][/tex]
6. Combine like terms:
[tex]\[ 3x - 5 = 4 \][/tex]
7. Add 5 to both sides to isolate the term with [tex]\(x\)[/tex]:
[tex]\[ 3x - 5 + 5 = 4 + 5 \][/tex]
[tex]\[ 3x = 9 \][/tex]
8. Finally, divide by 3 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{9}{3} \][/tex]
[tex]\[ x = 3 \][/tex]
Therefore, the solution is [tex]\(\boxed{3}\)[/tex].
1. Start with the given equation:
[tex]\[ \frac{x-1}{2} = \frac{x+2}{5} \][/tex]
2. Eliminate the fractions by finding a common denominator, which is 10 in this case. Multiply both sides of the equation by 10:
[tex]\[ 10 \cdot \frac{x-1}{2} = 10 \cdot \frac{x+2}{5} \][/tex]
3. Simplify both sides:
[tex]\[ 5(x - 1) = 2(x + 2) \][/tex]
4. Distribute the constants on both sides of the equation:
[tex]\[ 5x - 5 = 2x + 4 \][/tex]
5. Move all terms involving [tex]\(x\)[/tex] to one side of the equation and constants to the other side. Subtract [tex]\(2x\)[/tex] from both sides:
[tex]\[ 5x - 2x - 5 = 4 \][/tex]
6. Combine like terms:
[tex]\[ 3x - 5 = 4 \][/tex]
7. Add 5 to both sides to isolate the term with [tex]\(x\)[/tex]:
[tex]\[ 3x - 5 + 5 = 4 + 5 \][/tex]
[tex]\[ 3x = 9 \][/tex]
8. Finally, divide by 3 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{9}{3} \][/tex]
[tex]\[ x = 3 \][/tex]
Therefore, the solution is [tex]\(\boxed{3}\)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.